Multimodality imaging of renal lymphoma and its mimics - Trinh Nguyen; Akshya Gupta; Shweta Bhatt (Insights into Imaging, 2022)
Abstract Lymphomatous involvement of the genitourinary system, particularly the kidneys, is commonly detected on autopsies; yet on conventional diagnostic imaging renal lymphoma is significantly underestimated and underreported, in part due to its variable imaging appearance and overlapping features with other conditions. We present a spectrum of typical and atypical appearances of renal lymphoma using multimodality imaging, while reviewing the roles of imaging in the detection, diagnosis, staging, and surveillance of patients with lymphoma. We also illustrate a breadth of benign and malignant entities with similar imaging features confounding the diagnosis of renal lymphoma, emphasizing the role of percutaneous image-guided biopsy. Understanding the spectrum of appearances of renal lymphoma and recognizing the overlapping entities will help radiologists improve diagnostic confidence and accuracy.